2021
DOI: 10.1101/2021.06.07.447341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The fatty acid site is coupled to functional motifs in the SARS-CoV-2 spike protein and modulates spike allosteric behaviour

Abstract: The SARS-CoV-2 spike protein is the first contact point between the SARS-CoV-2 virus and host cells and mediates membrane fusion. Recently, a fatty acid binding site was identified in the spike (Toelzer et al. Science 2020). The presence of linoleic acid at this site modulates binding of the spike to the human ACE2 receptor, stabilizing a locked conformation of the protein. Here, dynamical-nonequilibrium molecular dynamics simulations reveal that this fatty acid site is coupled to functionally relevant regions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 74 publications
(104 reference statements)
2
17
0
Order By: Relevance
“…Equilibrium molecular dynamics (MD) simulations indicated persistent and stable interactions between LA and the spike trimer ( 13, 17 ), and that binding of LA rigidifies the FA binding site ( 17 ). Recently, in our previous work, using dynamical-nonequilibrium molecular dynamics (D-NEMD) simulations, we showed that the FA site is allosterically coupled to functional motifs for membrane fusion or with antigenic epitopes ( 29, 30 ). These simulations revealed that the removal of LA from the FA sites induces long-range structural responses in the receptor-binding motif (RBM), N-terminal domain (NTD), furin cleavage site and FP-surrounding regions ( 29, 30 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equilibrium molecular dynamics (MD) simulations indicated persistent and stable interactions between LA and the spike trimer ( 13, 17 ), and that binding of LA rigidifies the FA binding site ( 17 ). Recently, in our previous work, using dynamical-nonequilibrium molecular dynamics (D-NEMD) simulations, we showed that the FA site is allosterically coupled to functional motifs for membrane fusion or with antigenic epitopes ( 29, 30 ). These simulations revealed that the removal of LA from the FA sites induces long-range structural responses in the receptor-binding motif (RBM), N-terminal domain (NTD), furin cleavage site and FP-surrounding regions ( 29, 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in our previous work, using dynamical-nonequilibrium molecular dynamics (D-NEMD) simulations, we showed that the FA site is allosterically coupled to functional motifs for membrane fusion or with antigenic epitopes ( 29, 30 ). These simulations revealed that the removal of LA from the FA sites induces long-range structural responses in the receptor-binding motif (RBM), N-terminal domain (NTD), furin cleavage site and FP-surrounding regions ( 29, 30 ). D-NEMD simulations have also highlighted different allosteric and dynamical behaviours between the original (also known as ‘Wuhan’ or early 2020) spike and the D614G and BriSΔ (a variant containing an eight amino-acid deletion encompassing the furin recognition motif and S1/S2 cleavage site) variants ( 29, 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The same stabilizing effect of binding linoleic acids was proven by Toelzer et al using cryo-electron microscopy, and the linoleic acid binding was determined to be irreversible 53 , 54 . Furthermore, dynamical-nonequilibrium simulation results showed that the fatty acid binding site of the S protein can affect functionally important sites that are distant 55 . Another study stated that loss of lipids can destabilize the trimeric S protein and prevent receptor binding, however, the infectivity of released virus can be impacted by the nature of lipids that are present at the site of infection 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Our team identified a free fatty acid (FA) binding pocket at the RBD interfaces of the locked SARS-CoV-2 spike that was occupied by the essential fatty acid, linoleate (LA − ) in 2020 (8). Our previous simulations have shown that binding of LA − in the FA site helps to stabilize a locked conformation (9) which appears more condensed than the LA-free closed form) and that the carboxylate head group of the FA makes consistent salt-bridge interactions with the R408, occasional interactions with K417 and persistent H-bonding interactions with Q409, across the locked subunit interfaces (10). Fatty acids have since been retrospectively discovered in the FA sites of spike proteins from SARS viruses that infect other species (11, 12).…”
Section: Introductionmentioning
confidence: 99%